Sex-related Differences of Excoecaria agallocha L. with a View to Defence and Growth - Abdul Kader,; Sankar Narayan Sinha, (Tropical Life Sciences Research, 2022)
Excoecaria agallocha is a dioecious mangrove species, reported to have various medicinal properties. This study compares the gender-related biological activities between the sexes of E. agallocha in accordance with morpho-biochemical parameters which indicate their fitness over various environmental stresses as well as some information about the investment of their resources over defence and growth. For this investigation mature sun leaves of E. agallocha were collected from each sex from three different ecological regions like Bokkhali, Jharkhali, and Kolkata, West Bengal. The comparative study found that leaf of female plants yielded more compounds than males and also resulted higher anti-bacterial, reducing power, total antioxidant, and lipid peroxidation activities. Female leaves also showed higher concentrations of biochemical constituents like chlorophyll a, chlorophyll b, total carotenoids, total phenolic compounds and total protein content than male leaves. However, leaf area of all male leaves in all sites found to be greater than female leaves. The differences in growth rate and secondary metabolite content-based defences between sexes suggest that females invest resources in defences or resistance (Relative electrolytic leakages and TBARS content), whereas male invests their resources in growth (Leaf area) or tolerance. The present study strongly suggests that the female plant’s yields are more beneficial in terms of medicinal properties as compared to the male plant.